Channeling remittances to education: A field experiment among migrants from El Salvador - Ambler, Kate; Aycinena, Diego; Yang, Dean (American Economic Association, 2015)
We implement a randomized experiment offering Salvadoran migrants matching funds for educational remittances, which are channeled directly to a beneficiary student in El Salvador chosen by the migrant. The matches lead to increased educational expenditures, higher private school attendance, and lower labor supply of youths in El Salvador households connected to migrant study participants. We find substantial “crowd-in” of educational investments: for each $1 received by beneficiaries, educational expenditures increase by $3.72. We find no shifting of expenditures away from other students, and no effect on remittances. (JEL F24, I21, I22, J13, O15, O19)